Ketebalan Tunika Media Aorta Tikus Aterosklerosis Pasca Pemberian Ekstrak Buah Bakau (Rhizophora sp) - Muhammad Yulis Hamidy; Huriatul Masdar; Adham Alfian (Jurnal Ilmu Kedokteran, 2023)
Atherosclerosis is a multifocal immunoinflammatory disease of medium and large arteries stimulated by lipids, endothelial cells, leukocytes and intima smooth muscle cells. One of the markers of atherosclerosis is thickening of the tunica media. The administration of antioxidants is expected to inhibit the occurrence of atherosclerosis. Mangrove (Rhizophora sp) is one of plants with a high source of antioxidants. The objective of this study was to analyze the effect of mangrove (Rhizophora sp) fruit extract on the thickness of aortic tunica media of atherosclerotic rats. A total of eighteen rats were used in this study, divided into 3 groups. Group A (standard control) is a group of rats that received a standard diet. Group B (positive control) is a group of rats that received a high cholesterol diet for 3 days. Group C (treatment group), apart from receiving a high cholesterol diet, was also given Rhizophora sp fruit extract at a dose 500 mg/kg b.w/day orally for 3 days. The effect of mangrove (Rhizophora sp) fruit extract on the thickness of the aortic tunica media was evaluated by a histological procedure using the Leica application. This study shows that the thickness of aortic tunica media is higher in the group receiving a high cholesterol diet than the standard control group (0.096 vs. 0.079; P=0.036). The group that received mangrove (Rhizophora sp) fruit extract had relatively the same thickness as the standard group (0.080 vs. 0.079; P=0.999). As the conclusion, Mangrove (Rhizophora sp) fruit extract may inhibit thickening of the aortic tunica media in atherosclerotic rats.